Bar-HRM for authentication of plant-based medicines: Evaluation of three medicinal products derived from Acanthaceae species - Maslin Osathanunkul (2018)
© 2015 Osathanunkul et al. Medicinal plants are used as a popular alternative to synthetic drugs, both in developed and developing countries. The economic importance of the herbal and natural supplement industry is increasing every year. As the herbal industry grows, consumer safety is one issue that cannot be overlooked. Herbal products in Thai local markets are commonly sold without packaging or labels. Plant powders are stored in large bags or boxes, and therefore buying local herbal products poses a high risk of acquiring counterfeited, substituted and/or adulterated products. Due to these issues, a reliable method to authenticate products is needed. Here DNA barcoding was used in combination with High Resolution Melting analysis (Bar-HRM) to authenticate three medicinal Acanthaceae species (Acanthus ebracteatus, Andrographis paniculata and Rhinacanthus nasutus) commonly used in Thailand. The rbcL barcode was selected for use in primers design for HRM analysis to produce standard melting profiles of the selected species. Melting data from the HRM assay using the designed rbcL primers showed that the three chosen species could be distinguished from each other. HRM curves of all fifteen test samples indicated that three of tested products did not contain the indicated species. Two closely related species (A. paniculata and R. nasutus), which have a high level of morphological similarity, were interchanged with one another in three tested products. Incorrect information on packaging and labels of the tested herbal products was the cause of the results shown here. Morphological similarity among the species of interest also hindered the collection process. The Bar-HRM method developed here proved useful in aiding in the identification and authentication of herbal species in processed samples. In the future, species authentication through Bar-HRM could be used to promote consumer trust, as well as raising the quality of herbal products.